2012
DOI: 10.7554/elife.00065
|View full text |Cite
|
Sign up to set email alerts
|

The starvation hormone, fibroblast growth factor-21, extends lifespan in mice

Abstract: Fibroblast growth factor-21 (FGF21) is a hormone secreted by the liver during fasting that elicits diverse aspects of the adaptive starvation response. Among its effects, FGF21 induces hepatic fatty acid oxidation and ketogenesis, increases insulin sensitivity, blocks somatic growth and causes bone loss. Here we show that transgenic overexpression of FGF21 markedly extends lifespan in mice without reducing food intake or affecting markers of NAD+ metabolism or AMP kinase and mTOR signaling. Transcriptomic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
275
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(286 citation statements)
references
References 39 publications
10
275
1
Order By: Relevance
“…Furthermore, POLG mice fed chow have dramatically increased (4.7-fold) levels of fibroblast growth factor 21 (FGF21), an endocrine hormone known to mediate an adaptive response to starvation ( Fig. 1G) (12). Interestingly, HFD appears to synergistically increase FGF21 levels in POLG mice to roughly ninefold higher in comparison with WT mice fed chow or HFD (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, POLG mice fed chow have dramatically increased (4.7-fold) levels of fibroblast growth factor 21 (FGF21), an endocrine hormone known to mediate an adaptive response to starvation ( Fig. 1G) (12). Interestingly, HFD appears to synergistically increase FGF21 levels in POLG mice to roughly ninefold higher in comparison with WT mice fed chow or HFD (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, in this study we observed an upregulation of renal FGF21 mRNA in MR-fed mice compared to controls which may contribute to the insulin-sensitizing effects observed in the kidneys of these animals. FGF21 is a hormone released by the liver in response to caloric restriction and markedly extends the lifespan of mice when overexpressed (31). The kidney has been identified as a target of FGF21, and exogenous administration of FGF21 protein has been shown to improve systemic metabolism and exert antifibrotic properties in kidneys of db/db mice (16).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have shown that the mammalian lifespan-promoting hormone FGF21 (ref. 29) also controls female reproduction 30 and that its expression is regulated by the nuclear hormone receptors farnesoid X receptor and liver X receptor, both of which are NHR homologues, and is induced by bile acids similar to D 7 -DA 31,32 . Our findings therefore establish the molecular basis for the interplay between nutrition and reproduction in regulating lifespan.…”
Section: Daf-7(e1372);nhr-8(ok186) Bdmentioning
confidence: 99%